Cow health monitoring and disease detection - Ahmed, Safayet; Niloy, Tanjim Rahman; Hossain, Md Sazzad; Hossain, Khelafat; Shams, Kazi Ananda (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2023.